2004
DOI: 10.1073/pnas.0403929101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 315 genes essential for early zebrafish development

Abstract: We completed a large insertional mutagenesis screen in zebrafish to identify genes essential for embryonic and early larval development. We isolated 525 mutants, representing lesions in Ϸ390 different genes, and we cloned the majority of these. Here we describe 315 mutants and the corresponding genes. Our data suggest that there are roughly 1,400 embryonic-essential genes in the fish. Thus, we have mutations in Ϸ25% of these genes and have cloned Ϸ22% of them. Re-screens of our collection to identify mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
758
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(794 citation statements)
references
References 26 publications
32
758
0
4
Order By: Relevance
“…We wanted to determine the effects of an rps29 insertional mutation[14] on these waves in the zebrafish. Rps29 -/- embryos survive for five days[27], probably due to maternal rps29 protein deposited in the embryo. We previously showed that rps29 -/- embryos have decreased definitive HSC formation, likely the result of a defect in aorta specification[20].…”
Section: Resultsmentioning
confidence: 99%
“…We wanted to determine the effects of an rps29 insertional mutation[14] on these waves in the zebrafish. Rps29 -/- embryos survive for five days[27], probably due to maternal rps29 protein deposited in the embryo. We previously showed that rps29 -/- embryos have decreased definitive HSC formation, likely the result of a defect in aorta specification[20].…”
Section: Resultsmentioning
confidence: 99%
“…Another major advance in zebrafish forward genetic screens occurred with the application of a pseudotype retrovirus vector for insertional mutagenesis, enhancer trap and gene trap screens (Lin et al, 1994;Gaiano et al, 1996;Golling et al, 2002;Amsterdam et al, 2004). First developed as a vector for gene therapy and genetic studies, the engineered virus can infect a wide range of organisms and efficiently integrate into the genome.…”
Section: Insertional Mutagenesismentioning
confidence: 99%
“…Molecular identification of the Na, K-ATPase subunit atp1a1a.1 as the gene affected in m883 for the first time provides genetic evidence for the previously postulated role for an ion pump during establishment of laterality in general. Previously, four other zebrafish alleles of atp1a1a.1 were published (Shu et al, 2003;Amsterdam et al, 2004;Yuan and Joseph, 2004;Lowery and Sive, 2005). While the alleles published by Shu and coworkers (heart and mind, had) and Yuan and coworkers (small heart) appear to be identical, the insertional mutation published by Amsterdam and coworkers has not been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…A search for candidate genes in this region (www.ZFIN.org) revealed that Chen and colleagues had mapped the mutation heart and mind (had la1 ) to this genomic region and shown that had affects the gene ATPase, Naϩ/Kϩ transporting, alpha 1a.1 polypeptide (atp1a1a.1) (Shu et al, 2003). More recently, other alleles of had have also been published: had hi3475 , a retroviral insertion (Amsterdam et al, 2004), had mw15b (Yuan and Joseph, 2004), and had to273a (Lowery and Sive, 2005), which initially had been described as snk to273a . In collaboration with Dr. Chen (UCLA), we performed complementation analysis of m883 and had la1 , which revealed non-complementation and demonstrated that m883 is an allele of had.…”
Section: The M883 Mutation Causes Left-right Isomerism Of Endodermal mentioning
confidence: 99%